Intellectual changes after radiation for children with brain tumors: which brain structures are most important?. Issue 3 (16th September 2020) - Tsang, Derek S; Kim, Laurence; Liu, Zhihui Amy; Janzen, Laura; Khandwala, Mohammad; Bouffet, Eric; Laperriere, Normand; Dama, Hitesh; Keilty, Dana; Craig, Tim; Ramaswamy, Vijay; Hodgson, David C; et al.
Abstract: Background: The objective of this study was to evaluate the contribution of radiation dose to different intracranial structures on changes in intellectual function for children with brain tumors. Methods: We evaluated children with brain tumors treated in 2005–2017 who had longitudinal neuropsychological assessments and available photon dosimetric data (if radiation therapy [RT] given). Full Scale Intelligence Quotient (FSIQ) and index scores were evaluated (perceptual reasoning index [PRI], processing speed index [PSI], verbal comprehension index [VCI], and working memory index [WMI]). Multivariable linear mixed effects models were used to model endpoints, with age at RT and dose to different brain regions as fixed effects and patient-specific random intercepts. P -values (P*) were adjusted for multiple comparisons. Results: Sixty-nine patients were included, 56 of whom received RT. Median neuropsychological follow-up was 3.2 years. Right temporal lobe mean dose was strongly associated with decline in FSIQ ( P * = 0.005); with each gray increase in mean dose, there was a decrease of 0.052 FSIQ points per year. Dose to 50% (D50) of the supratentorial brain was associated with decline in PSI ( P * = 0.006) and WMI ( P * = 0.001). Right and left hippocampus D50 were individually strongly associated with declines in VCI ( P * = 0.009 for each). Presence of a ventriculoperitoneal shunt decreased FSIQ by 10 points. Conclusions: We reported associations between dosimetry to specific brain regions and intellectual outcomes, with suggested avoidance structures during RT planning. These models can help clinicians anticipate changes in neurocognition post-RT and guide selection of an optimal RT plan.